Feasibility Assessment of the Reebok CHECKLIGHT™ and King-Devick tests as Screening tools in Youth Football - Brent Harper; Adrian Aron; Alex Siyufy; Angela Mickle; Ken Cox (Bowling Green State University, 2018)
Background: Concussions are one of the foremost issues in sport, with football having one of the highest incidence rate of injury. Moreover, there is a need to monitor sub-concussive head impacts because they do not initiate further assessment which may increase an athlete's risk of suffering a brain injury. The purpose of this article is to discuss the viability of use for the Reebok CHECKLIGHT™ system and its correlation to concussive events screening in two levels of football: youth recreation league football (ages 11-13) and high school football (ages 13-18). Results: The Reebok CHECKLIGHT™ system activation did not correlate with the King-Devick score (r=-0.08, p=0.7). There was no difference between the two levels of football in the number of times the lights came on, 1.77 ± 2.05 vs. 1.42 ± 0.79, p=0.57. Limitation: The viability of CHECKLIGHT™ system was limited by threshold issues with the light alert system, light usefulness, set-up, and implementation. Conclusion: The Reebok CHECKLIGHT™ system may be beneficial to individual athletes below the high school level; however, it appears to have limited usefulness for entire teams and/or high school athletes.